A Shape‐Adaptive, Antibacterial‐Coating of Immobilized Quaternary‐Ammonium Compounds Tethered on Hyperbranched Polyurea and its Mechanism of Action. (8th August 2013) - Asri, Lia A. T. W.; Crismaru, Mihaela; Roest, Steven; Chen, Yun; Ivashenko, Oleksii; Rudolf, Petra; Tiller, Joerg C.; van der Mei, Henny C.; Loontjens, Ton J. A.; Busscher, Henk J.
<x xml:space="preserve">Abstract</x> Quaternary‐ammonium‐compounds are potent cationic antimicrobials used in everyday consumer products. Surface‐immobilized, quaternary‐ammonium‐compounds create an antimicrobial contact‐killing coating. We describe the preparation of a shape‐adaptive, contact‐killing coating by tethering quaternary‐ammonium‐compounds onto hyperbranched polyurea coatings, able to kill adhering bacteria by partially enveloping them. Even after extensive washing, coatings caused high contact‐killing of Staphylococcus epidermidis, both in culture‐based assays and through confocal‐laser‐scanning‐microscopic examination of the membrane‐damage of adhering bacteria. In culture‐based assays, at a challenge of 1600 CFU/cm2, contact‐killing was >99.99%. The working‐mechanism of dissolved quaternary‐ammonium‐compounds is based on their interdigitation in bacterial membranes, but it is difficult to envisage how immobilized quaternary‐ammonium‐molecules can exert such a mechanism of action. Staphylococcal adhesion forces to hyperbranched quaternary‐ammonium coatings were extremely high, indicating that quaternary‐ammonium‐molecules on hyperbranched polyurea partially envelope adhering bacteria upon contact. These lethally strong adhesion forces upon adhering bacteria then cause removal of membrane lipids and eventually lead to bacterial death.